Non-invasive cancer detection in canine urine through Caenorhabditis elegans chemotaxis - Namgong, Chan; Kim, Jong Hyuk; Lee, Myon Hee; Midkiff, Daniel (Frontiers in Veterinary Science, 2022)
Cancer is the leading cause of death of companion animals, and successful early treatment has been a challenge in the veterinary field. We have developed the Non-Invasive Cancer Screening (N.C.S.) Study to perform cancer detection through the analysis of canine urine samples. The test makes use of the strong olfactory system of the nematode Caenorhabditis elegans, which was previously shown to positively respond to urine samples from human cancer patients. We performed a proof-of-concept study to optimize the detection capability in urine samples obtained from dogs with naturally occurring cancers. In this study, we established a scale for identifying the cancer risk based on the magnitude of the chemotaxis index of C. elegans towards a canine urine sample. Through validation, the N.C.S. Study achieved a sensitivity of 85%, showing that it is highly sensitive to indicating the presence of cancer across multiple types of common canine cancers. The test also showed a 90% specificity to cancer samples, indicating a low rate of over-identifying cancer risk. From these results, we have demonstrated the ability to perform low-cost, non-invasive cancer detection in companion animals, a method which can increase the ability to perform cancer diagnosis and treatment.